Robotic Process Automation (RPA) in the internal audit of large companies in Medellín, Colombia: Implementation and lessons learned - Jonathan David Armijo-Perea; Sofía Sepúlveda; Isabella Velásquez; Eduart Villanueva (Multidisciplinary Business Review)
Internal audits have incorporated technologies such as Robotic Process Automation (RPA) to transform their practices due to the challenges of the modern business environment. Therefore, this study aimed to identify the various stages and lessons learned from adopting RPA in the internal audit process of large companies in Medellín, Colombia. The research had a qualitative approach of descriptive scope with a multiple case study through semi-structured interviews. It was found that RPA was implemented only in audit tests with mostly positive results and with differentiated success rates according to the technological infrastructure available; interviewees report increases in audit efficiency and coverage with more time dedicated to strategic activities and not to repetitive activities that can be automated with this technology.